THE IMPACT OF THE GREEN ECONOMY DEVELOPMENT STRATEGY ON OPERATIONAL EFFICIENCY OF ECOTOURISM BUSINESSES - Nguyen Van Nhung (HUIT Journal of Science, 2025)
The article examines the impact of green economy development strategy on the operational performance of ecotourism enterprises in Vietnam. Research results indicate 5 influencing factors including: (1) Digital technology application in tourism (DTA); (2) Digital transformation support policies (DTS); (3) Sustainable tourism startup ecosystem (STE); (4) Raising community awareness of green tourism (RCA) and (5) Business model innovation in tourism (BMI). Based on these research findings, the author proposes several management implications to help ecotourism enterprises develop solutions to improve operational performance and promote sustainable tourism development in the context of green economy.